Czech Cheeses: Their History, Production, and Chemical and Sensory Qualities - Martín-Del-Campo, Sandra Teresita; Pérez-Alva, Alexa; Baigts-Allende, Diana Karina (Journal of food science, 2025)
This study presents a comprehensive overview of the most well-known Czech cheeses. It starts with an overview of the three Protected Geographical Indication (PGI) cheeses, followed by a summary of other traditional or well-appreciated cheeses. The cheese-making industry has experienced constant growth, and European cheeses are appreciated globally and locally. The Czech cheese industry is not the exception. However, despite the Czech cheese-making tradition, there is a dearth of scientific knowledge. Most information is outdated, and access to historical databases is insufficient. For the Czech cheeses evaluated in this study, the cheese-making process, alongside the available compositional and functional information, is described when possible. The PGI Olomoucké tvarůžky, Jihočeská Niva, Jihočeská Zlatá Niva cheeses, and the non-protected Blat'ácke zlato cheese have more extensive scientific information presented. Other traditional Czech cheeses, such as Romadur, Nalžov, or Sázava, could be granted a PGI if research provides deeper knowledge about the impact of culture, production region, processes, and ripening, among others, in their unique characteristics.
Keywords: Cheese; sýr; chuť; dějiny 20. století; Food Handling; Humans; Česká republika; History, 20th Century; lidé; dějiny 21. století; Taste; manipulace s potravinami; History, 21st Century; Czech Republic